Instruments, Measurement Principles and Communication Technologies for Downhole Drilling Environments - Gooneratne, Chinthaka P.; Li, Bodong; Deffenbaugh, Max; Moellendick, Timothy (Smart Sensors, Measurement and Instrumentation, 2019)
This book presents a complete review of the unique instruments and the communication technologies utilized in downhole drilling environments. These instruments and communication technologies play a critical role in drilling hydrocarbon wells safely, accurately and efficiently into a target reservoir zone by acquiring information about the surrounding geological formations as well as providing directional measurements of the wellbore. Research into instruments and communication technologies for hydrocarbon drilling has not been explored by researchers to the same extent as other fields, such as biomedical, automotive and aerospace applications. Therefore, the book serves as an opportunity for researchers to truly understand how instruments and communication technologies can be used in a downhole environment and to provide fertile ground for research and development in this area. A look ahead, discussing other technologies such as micro-electromechanical-systems (MEMS) and fourth industrial revolution technologies such as automation, the industrial internet of things (IIoT), artificial intelligence, and robotics that can potentially be used in the oil/gas industry are also presented, as well as requirements still need to be met in order to deploy them in the field.